Mekanisme Corporate Governance, Manajemen Laba Dan Kinerja Keuangan Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Di Bursa Efek Indonesia Tahun 2011-2015 - Saroyo, Dorry Paramitasari, Zulfa Irawati, SE, M.Si (2017)
This research is meant to examine the effect of Corporate Governance Mechanism on Earnings Management. The study also examined the consequences of the influence mechanism of Corporate Governance and Earnings Management to Financial Performance. This study used a sample of 17 companies of Basic Industry and Chemicals listed in Indonesia Stock Exchange, using purposive sampling which publishes financial statements from 2011-2015. Based on the result only the Size of the Board of Commissioners and Earnings Management affecting Financial Performance, making it necessary to use the model 3. The results concluded that the effect on the Corporate Governance of Earnings Management, Corporate Governance affect the Financial Performance, Earnings Management just does not affect the Financial Performance. The conclusion showed that 0,044 (P2 x P3) < 0.180 (P1), the Earnings Management is not an intervening variable under the influence of Corporate Governance to the Financial Performance.